Efektivitas Penertiban Nota Hasil Intelijen Dalam Rangka Pengawasan Barang Ekspor Di Kantor Pelayanan Utama Bea Dan Cukai Tipe A Tanjung Priok Tahun 2024 - Novlyani, Citra; Rizkiansyah, Ahdiat; Malik, Deni (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Supervision of export activities plays a crucial role in maintaining exporter compliance and preventing potential violations that may lead to state revenue losses. One of the strategic instruments employed by the Directorate General of Customs and Excise is the Nota Hasil Intelijen (NHI), which serves as an early detection tool for potential violations in export activities. This study aims to analyze the effectiveness of export goods supervision based on NHI at the Main Customs Office (KPUBC) Type A Tanjung Priok in 2024, using the effectiveness framework proposed by Martani and Lubis in Hermawan (2017), which includes the resource approach, process approach, and goals approach. This research adopts a qualitative method with a case study approach. Data were collected through in-depth interviews with six key informants from internal DJBC personnel and business actors, supported by secondary data such as performance reports (LAKIN), standard operating procedures (SOP), and NHI export statistics. The research findings indicate that NHI-based export supervision at KPUBC Tanjung Priok is highly effective, with a 95,83% follow-up rate and various forms of enforcement, including export cancellation, investigation, and seizure of goods by the state. The challenges identified include limitations in human resources, facilities, and technical disruptions in the field. To address these issues, several efforts have been made, such as technical training, inter-unit coordination, and the use of digital documentation tools. In conclusion, the implementation of NHI has significantly improved export compliance and violation prevention, although further strengthening is needed in terms of human resources and operational infrastructure.